The digital transformation of the European border regime: the powers and perils of imagining future borders - Trauttmansdorff, Paul (Bristol University Press, 2024)
This book offers an in-depth investigation into the digitizsation processes of Europes border regime. With a focus on the European Union agency eu-LISA, one of the most significant actors in the digital border regime, it shows how sociotechnical imaginations drives the future of borders and European governance of mobility